Development of Ethnomathematics-Based E-Module Using the Inquiry Learning Model to Improve Mathematical Problem Solving Ability (Unnes Journal of Mathematics Education, 2022)
The purpose of this research was to produce an ethnomathematics-based e-module development on an inquiry learning model that was valid, practical, and effective in improving students' mathematical problem-solving ability. This study used the Research and Development (R&D) method with the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used questionnaires and tests. The data analysis technique used a Likert scale, the one-sided average test, and the two-sided average difference test. The results of this study indicate that e-module have very valid criteria for use in the learning process with an average validity percentage of 88.54%, e-module have very practical criteria for use in the learning process with an average practicality percentage of 87.33%, and e-module are categorized as effective or can improve students' mathematical problem-solving ability, which is indicated by (a) students' mathematical problem-solving ability with ethnomathematics-based e-modules using the inquiry learning model to achieve mastery criteria; (b) students' mathematical problem-solving ability with ethnomathematics-based e-modules using inquiry learning models are better than students' mathematical problem-solving ability in conventional learning.